2008
DOI: 10.1152/ajpheart.01312.2007
|View full text |Cite
|
Sign up to set email alerts
|

Improved ECG detection of presence and severity of right ventricular pressure load validated with cardiac magnetic resonance imaging

Abstract: Henkens IR, Mouchaers KT, Vonk-Noordegraaf A, BoonstraA, Swenne CA, Maan AC, Man S, Twisk JW, van der Wall EE, Schalij MJ, Vliegen HW. Improved ECG detection of presence and severity of right ventricular pressure load validated with cardiac magnetic resonance imaging. The study aimed to assess whether the 12-lead ECG-derived ventricular gradient, a vectorial representation of ventricular action potential duration heterogeneity directed toward the area of shortest action potential duration, can improve ECG diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
41
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 37 publications
5
41
2
Order By: Relevance
“…Furthermore, instead of an increase in the ventricular gradient that would be associated with increased heterogeneity of action potential duration (20), the ventricular gradient decreased. This is consistent with the notion that the net left ventricular contribution to the QRS T integral is effectively cancelled by enhanced terminal RV conduction delay, a process previously observed in patients with pulmonary arterial hypertension (24).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, instead of an increase in the ventricular gradient that would be associated with increased heterogeneity of action potential duration (20), the ventricular gradient decreased. This is consistent with the notion that the net left ventricular contribution to the QRS T integral is effectively cancelled by enhanced terminal RV conduction delay, a process previously observed in patients with pulmonary arterial hypertension (24).…”
Section: Discussionsupporting
confidence: 92%
“…Most importantly, heart rate increases and the magnitude and direction of ventricular de-and repolarisation forces change due to increased RV wall stress and hypertrophy [10][11][12]. Previous studies demonstrated that the electrocardiographically derived ventricular gradient (VG) can accurately detect increased pulmonary pressures when projected in the optimal direction for detection of RV pressure overload (VG-RVPO) in a heterogeneous population suspected of PH [10,12,13]. However, the value of the VG-RVPO is still unknown in patients with SSc, who are at increased risk for development of PH.…”
Section: Introductionmentioning
confidence: 99%
“…This is associated with decreased K ϩ channel activity, although studies disagree precisely which channels (26,27,32,41). Interestingly, the changes in ventricular gradient and QT interval seen in human PAH (17,19,20) are also seen in the MCT model (16,27,32). These observations would predict that the MCT model is proarrhythmic, but this has not previously been directly investigated.…”
mentioning
confidence: 96%
“…In humans, pulmonary artery hypertension (PAH) is a disease that can be unstable and RV failure is a common outcome (4,13,38). The QT interval and QT dispersion of the ECG have been reported to be increased (19,20), and the shift in ECG derived ventricular gradient [reflecting action potential duration (APD) dispersion] has been related to increased RV load (17). Such changes in electrical activity have been linked to arrhythmias (1,39), and PAH is associated with arrhythmias in patients (11).…”
mentioning
confidence: 99%